Idea house : future tropical living today - Pomeroy, Jason (Singapore : Oro Editions, 2011)
The Idea House is the first zero carbon prototype in Asia. This book documents the process of design required to create a carbon neutral development from inception to completion, and provides an insight into sustainable tropical living.
One world -- Team -- Idea -- House -- Community.
Includes bibliographical references and index.
Keywords: SUSTAINABLE ARCHITECTURE -- DESIGN AND CONSTRUCTION -- MALAYSIA